Ba4FeAgS6: a new antiferromagnetic and semiconducting quaternary sulfide. Issue 3 (25th November 2022) - Panigrahi, Gopabandhu; Yadav, Sweta; Jana, Subhendu; Ramanujachary, K. V.; Niranjan, Manish K.; Prakash, Jai
Abstract : A new one-dimensional antiferromagnetic and semiconducting quaternary sulfide Ba4 FeAgS6 has been synthesized and its physical properties have been investigated in detail. Abstract : The single crystals of a quaternary sulfide, Ba4 FeAgS6, have been synthesized by reacting elements at 873 K inside a sealed fused silica tube. The title phase is the first ordered quaternary compound of the Ba–Ag–Fe–S system. The crystal structure of Ba4 FeAgS6 is characterized by a single-crystal X-ray diffraction study at 298(2) K. It crystallizes in the space group C 52h – P 21 / n of the monoclinic crystal system with unit cell dimensions of a = 8.6367(5) Å, b = 12.0291(7) Å, c = 13.2510(7) Å, and β = 109.015(2)°. This compound is stoichiometric, and its structure contains twelve unique crystallographic sites: four Ba, one Fe, one Ag, and six S sites. All atoms of the structure occupy the general positions. The Ba4 FeAgS6 structure consists of one-dimensional chains of 1∞[FeAgS6 ] 8− that are extended in the [100] direction. The negative charges on these chains are counterbalanced by the filling of Ba 2+ cations in between the 1∞[FeAgS6 ] 8− chains. The Fe atoms are bonded to four S atoms that form a distorted tetrahedral geometry around the central Fe atom. Each Ag atom in this structure is coordinated with four S atoms in a distorted tetrahedral fashion. These FeS4 and AgS4 motifs are the main building blocks of the Ba4 FeAgS6 structure. The corner-sharing of FeS4 and AgS4 tetrahedra creates one-dimensional chains of 1∞[FeAgS6 ] 8− . This structure does not contain any homoatomic or metallic bonds and can be charge-balanced as (Ba 2+ )4 (Fe 3+ )1 (Ag 1+ )1 (S 2− )6 . The optical absorption study performed on a polycrystalline Ba4 FeAgS6 sample reveals a direct bandgap of 1.2(1) eV. The magnetic studies reveal the antiferromagnetic behavior of Ba4 FeAgS6 below 50 K. The thermal conductivity and theoretical electronic structure of Ba4 FeAgS6 are also studied in detail.